Mechanically induced development and maturation of human intestinal organoids in vivo. (June 2018) - Poling, Holly; Wu, David; Brown, Nicole; Baker, Michael; Hausfeld, Taylor; Huynh, Nhan; Chaffron, Samuel; Dunn, James; Hogan, Simon; Wells, James; Helmrath, Michael; Mahe, Maxime
Abstract The natural ability of stem cells to self-organize into functional tissue has been harnessed for the production of functional human intestinal organoids. Although dynamic mechanical forces play a central role in intestinal development and morphogenesis, conventional methods for the generation of intestinal organoids have relied solely on biological factors. Here, we show that the incorporation of uniaxial strain, using compressed nitinol springs, in human intestinal organoids transplanted into the mesentery of mice induces growth and maturation of the organoids. Assessment of morphometric parameters, transcriptome profiling and functional assays of the strain-exposed tissue revealed higher similarities to native human intestine, with regard to tissue size and complexity, and muscle tone. Our findings suggest that the incorporation of physiologically relevant mechanical cues during the development of human intestinal tissue enhances its maturation and enterogenesis. Uniaxial strain provided by compressed nitinol springs incorporated in human intestinal organoids transplanted into the mouse mesentery enhances organoid growth and maturation, and improves the similarity of the organoids to native human intestine.